Are levels of coping with stress in pregnancy with gestational diabetes worse than in healthy pregnancy? - Hamdiye Arda Sürücü; Dilek Büyükkaya Besen; Mesude Duman; Elif Yeter Erbil; İshak Ay (Taylor & Francis Group, 2019)
Purpose: The purpose of this study was to analyze the levels of coping with stress in healthy pregnant women in comparison with the levels of coping with stress in pregnant women with gestational diabetes mellitus (GDM). Materials and methods: In the study, the descriptive cross-sectional research design was used. The study was carried out with 218 pregnant women in total. Results: It was found that the healthy pregnant women had a higher total score for coping with stress and used the self-confident coping style, one of the effective coping styles, more frequently when compared to the pregnant women with GDM (p < .001). In addition, the pregnant women with GDM used the desperate coping style, one of the ineffective coping styles, more frequently than the healthy pregnant women (p < .001). Conclusions: Diabetes education that nurses give should allow not only the nurses to evaluate the coping levels of pregnant women with GDM, but also to teach these pregnant women how to use effective coping styles.